Penanaman Sikap Sabar dalam Membentuk Sikap Religius Anak Usia Dini pada Animasi Si Bulan Koki Super - Putri, Talita Kenanga; Nurjanah, Nurjanah (ALSYS, 2025)
One of the media that represents the role of mothers in instilling Islamic values is the animation Si Bulan Koki Super. This study aims to examine the Islamic values instilled by the Mother character in the show, as well as how her role in shaping religious attitudes in early childhood. This research was conducted with a qualitative approach through the content analysis method, with data obtained from observation and documentation of one episode, namely “Minggu Pagi Si Bulan dan Meong Jualan Kue!?” (“anak kukuk ruyuk”). The results of the analysis show that Bunda's character not only appears as a mother but also as an educator who consistently instills Islamic values such as patience. These values are conveyed through modeling, giving advice, and linking religious teachings with daily activities. This animation show has a positive impact, not only for children as the main audience, but also for parents who can use it as inspiration in educating children in an Islamic manner.